2018
DOI: 10.1002/term.2708
|View full text |Cite
|
Sign up to set email alerts
|

Silica-gelatin hybrid sol-gel coatings: A proteomic study with biocompatibility implications

Abstract: Osseointegration, including the foreign body reaction to biomaterials, is an immune-modulated, multifactorial, and complex healing process in which various cells and mediators are involved. The buildup of the osseointegration process is immunological and inflammation-driven, often triggered by the adsorption of proteins on the surfaces of the biomaterials and complement activation. New strategies for improving osseointegration use coatings as vehicles for osteogenic biomolecules delivery from implants. Natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In vivo, it has been shown MT increases the formation of new bone trabeculae with higher relative length and density than Ti. 26,27 However, as described by Araujo-Gomes et al, 17,28 MT does not induce changes ALP activity when compared to Ti, even though it increases the expression of IL-6 and osteocalcin (OCN) expression. In co-cultures, mainly collagens (CO5A1, CO3A1, CO6A1, CO6A2, CO1A2, CO1A1, CO6A3) were down-Table 4.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In vivo, it has been shown MT increases the formation of new bone trabeculae with higher relative length and density than Ti. 26,27 However, as described by Araujo-Gomes et al, 17,28 MT does not induce changes ALP activity when compared to Ti, even though it increases the expression of IL-6 and osteocalcin (OCN) expression. In co-cultures, mainly collagens (CO5A1, CO3A1, CO6A1, CO6A2, CO1A2, CO1A1, CO6A3) were down-Table 4.…”
Section: Discussionmentioning
confidence: 90%
“…Martínez-Ibáñez et al characterized MT in vitro with human adipose tissue-derived mesenchymal stem cells (AMSCs) showing that the material increased calcium-rich deposit formation. In vivo, it has been shown MT increases the formation of new bone trabeculae with higher relative length and density than Ti. , However, as described by Araújo-Gomes et al, , MT does not induce changes ALP activity when compared to Ti, even though it increases the expression of IL-6 and osteocalcin (OCN) expression. In co-cultures, mainly collagens (CO5A1, CO3A1, CO6A1, CO6A2, CO1A2, CO1A1, CO6A3) were downregulated, while ALP was lower at 14 days.…”
Section: Discussionmentioning
confidence: 94%
“…Although many publications describe how proteins condition bone healing, a deeper and detailed knowledge of cellular function including inflammation and osteointegration remains unclear for some of the identified proteins. Especially there are only a few studies trying to understand how defined types of biomaterials can influence the protein adsorption onto surfaces …”
Section: Resultsmentioning
confidence: 99%
“…The data imply that complement proteins, including C1, factor H, and C4b-binding protein, which were found to be enriched on the surface, crucially contributed to the fibrous capsule formation observed [ 84 ]. In contrast, the same group demonstrated that in case of an in vivo rabbit tibia implant, high levels of adsorbed complement proteins (C1q and factor D) to the coated titanium surface did not negatively affect osseointegration [ 85 ]. These studies show that detailed analysis of the implant-bound proteome and “complementome” might allow a prediction of the material’s behavior in vivo, which could be superior to current in vitro tests that do not sufficiently reflect the in vivo situation [ 86 ].…”
Section: Potential Role Of the Complement System In The Immune Resmentioning
confidence: 99%